Targeting Myeloid-Derived Cells: New Frontiers in the Treatment of Non-alcoholic and Alcoholic Liver Disease - Vonghia, Luisa; Van Herck, Mikhaïl A.; Weyler, Jonas; Francque, Sven (Frontiers in Immunology, 2019)
Non-alcoholic fatty liver disease (NAFLD) and Alcoholic Liver Disease (ALD) are major causes of liver-related morbidity and mortality and constitute important cause of liver transplantation. The spectrum of the liver-disease is wide and includes isolated steatosis, steatohepatitis and cirrhosis. The treatment of NAFLD and ALD remains, however, an unmet need, and therefore it is a public health priority to develop effective treatments for these diseases. Alcoholic and non-alcoholic liver disease share common complex pathogenetic pathways that involve different organs and systems beyond the liver, including the gut, the adipose tissue and the immune system, which cross-talk to generate damage. Myeloid-derived cells have been widely studied in the setting of NAFLD and ALD and are implicated at different levels in the onset and progression of this disease. Among these cells, monocytes and macrophages have been found to be involved in the induction of inflammation and in the progression to fibrosis, both in animal models and clinical studies and they have become interesting potential targets for the treatment of both NAFLD and ALD. The different mechanisms by which these cells can be targeted include modulation of Kupffer cell activation, monocyte recruitment in the liver and macrophage polarization and differentiation. Evidence from preclinical studies and clinical trials (some of them already in phase II and III) have shown encouraging results in ameliorating steatohepatitis, fibrosis and the metabolic profile, individuating promising candidates for the pharmacological treatment of these diseases. The current available results of myeloid-derived cells targeted treatments in NAFLD and ALD are covered in this review.